(3eNJUQ VjGAGdfgGQ GdoeLdj dZeGe GdCHUGQ aj fUQI Cgd GdSfIs - (3CHhGdbGSe Ydj Hf MLQs
(3ChdgG (B:s
(3CeG HYO agPg fHPI aj fUQI Cgd GdPcQ HGdeJGhHI hGdLeGYI s
(3BNQgG (B:s
(3gPG ef YGej gPG Edi jhe GdbjGeI JeJ HMeO Gddg hMSf Yhfg s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRfI GdYGe HGdQHGW (B- (3GdeZQH (B(D 115) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs